Investment and Minimum Wages: Evidence from Indonesia Food and Beverage Manufacturing Industry - Rachman, Muchammad Bintang Cahyo Andhika; Wasil, Mohammad (PT Keberlanjutan Strategis Indonesia, 2026)
This study analyzes the effect of Domestic Investment, Provincial Minimum Wage, and Foreign Investment on the Gross Regional Domestic Product (GRDP) of the Food and Beverage Processing Industry in Indonesia during the period 2014–2024. The research employs a quantitative approach using secondary data obtained from the Central Statistics Agency (BPS). Panel data from 38 provinces are utilized, and the Random Effect Model is selected as the most appropriate estimation method. The results indicate that Domestic Investment does not have a significant effect, while the Provincial Minimum Wage and Foreign Investment have a significant effect on the GRDP of the Food and Beverage Processing Industry. These findings are in line with the current government priority programs, namely industrial downstreaming and the Free Nutritious Meal Program. Therefore, this study is expected to provide policy recommendations for the government in strengthening industrial competitiveness, improving workers’ welfare, and supporting the success of current and future government programs